Vectors of the Sociology of Religion in the European Sociological Association - Ксения Медведева (Russian Sociological Review, 2016)
This review examines the key issues of the international conference of the European Sociological Association (ESA) held in August 2015 in Prague (Czech Republic). It gives an outline of the plenary speech by A. Hochschild at the opening of the conference dedicated to the connection between emotions and political beliefs. The review focuses on the key debates in contemporary European sociology of religion that were held during the 15 sessions held by the research network of sociologists of religion of ESA. Such vectors as conflict, identity, religion and state are highlighted. Special attention is paid to gender issue, women priests and bisexual Christians. The diversity of types of social inequality in the context of various religions and regions of the world is discussed, in particular, in Europe and Near East. Reports by Russian sociologists of religion are indicated. Particular attention is given to the papers on monasticism as a role model for religious actors in Buddhism and Christianity. It is shown that institutional changes in monasticism may cause signal the changes in the role religion in society. The review examines a research on monasticism as a traditional institution in Christianity using the example of the Roman Catholic church in Switzerland and as an innovative institution in Buddhism using the case of a Buddhist community in Spain. The structure, history, current status and future academic plans of the ESA research network of the sociologists of religion are analyzed. The interdisciplinary potential of the sociology of religion and thematic areas connected with the study of religion by other research networks and are covered, including culture, migration and gender studies.